A Reference Architecture for Developing Resource-Limited Disease Surveillance Systems - Agung Fatwanto (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2012)
In recent years, several countries have developed and implemented disease surveillance systems. These systems, eventhough having relatively similar functions, are adopting different approaches. Based on a preliminary study, an effective strategy for developing a disease surveillance system was proposed. This paper proposes a reference architecture for building a disease surveillance system based on the medical and technological perspective in the context of resource-limited environment.